The Semitic Languages an International Handbook. - Weninger, Stefan; Khan, Geoffrey; Streck, Michael P.; Watson, Janet C. E. (Berlin : De Gruyter Mouton, 2011)
The Handbook of Semitic Languages offers a comprehensive reference tool for Semitic Linguistics in its broad sense. It is not restricted to comparative Grammar, although it covers also comparative aspects, including classification. By comprising a chapter on typology and sections with sociolinguistic focus and language contact, the conception of the book aims at a rather complete, unbiased description of the state of the art in Semitics. Articles on individual languages and dialects give basic facts as location, numbers of speakers, scripts, numbers of extant texts and their nature, attestatio.
60. Arabic-Persian Language Contact61. Language Contact between Arabic and Modern European Languages; 62. Maltese as a National Language; 63. Ancient South Arabian; 64. Modern South Arabian; VII. The Semitic Languages and Dialects V: Ethio-Semitic Languages; 65. Ethio-Semitic in General; 65. Old Ethiopic; 66. Tigre; 67. Tigrinya; 68. Tigrinya as National Language of Eritrea and Tigray; 69. Amharic; 70. The Role of Amharic as a National Language and an African lingua franca; 71. Gurage; 72. Harari; 73. Ethiosemitic-Cushitic Language Contact; Terminological index.
Description based on print version record.
Keywords: Semitic languages -- Grammar -- Handbooks, manuals, etc; Semitic languages -- History -- Handbooks, manuals, etc; Semitic languages; Language and languages; Semitic languages -- History -- Handbooks, manuals, etc; Semitic languages -- Grammar -- Handbooks, manuals, etc; FOREIGN LANGUAGE STUDY / Arabic; Electronic books